2020
DOI: 10.21608/eajbsf.2020.75972
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance and efficacy evolved in field populations of Spodoptera littoralis in Egypt cotton season

Abstract: The journal of Toxicology and pest control is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the interaction between insects and their environment. The goal of the journal is to advance the scientific understanding of mechanisms of toxicity. Emphasis will be placed on toxic effects observed at relevant exposures, which have direct impact on safety evaluation and risk assessment. The journal therefore welcomes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…In contrast, Elhadek (2021) evaluated the resistance status for IGRs in Menofia and Gharbia governorate in Egypt and found no resistance developed in S. littoralis field strains comes from both sides. Also, Elhadek et al (2020) reordered very low resistance ratios values to Lufenuron, Chlorflauzuron, and Diflubenzuron in Menofia and Gharbia field strains. Therefore, continuous evaluation of ICRs efficacy and susceptibility are in demand to avoid resistance and cross resistance development.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, Elhadek (2021) evaluated the resistance status for IGRs in Menofia and Gharbia governorate in Egypt and found no resistance developed in S. littoralis field strains comes from both sides. Also, Elhadek et al (2020) reordered very low resistance ratios values to Lufenuron, Chlorflauzuron, and Diflubenzuron in Menofia and Gharbia field strains. Therefore, continuous evaluation of ICRs efficacy and susceptibility are in demand to avoid resistance and cross resistance development.…”
Section: Discussionmentioning
confidence: 91%
“…Abdel-Mageed et al (2006) reported that spinosad gave moderately initial and residual effects when tested alone. (Elhadek, Hafez, and Ali 2020) indicates the high efficacy of some IGRs and Bioinsecticides to be used as an effective alternative method of S. littoralis control while insecticide resistance has developed for other traditional insecticides.…”
mentioning
confidence: 99%